Case report of a giant cervical leiomyoma - Chen, Fang; Bai, Feng; Wang, Yang; Li, Wenjuan (Frontiers in Medicine, 2025)
This article reports the clinical diagnosis and treatment of a 42-year-old female patient with a giant cervical leiomyoma, a rare condition. A review of the literature over the past 30 years reveals only one reported case of a cervical interstitial leiomyoma larger than 20 cm. The surgical removal of such a large cervical smooth muscle tumor poses significant challenges. Due to the cervical location deep within the pelvis and its proximity to several vital organs, the presence of a giant tumor increases the risk of intraoperative bleeding and potential injury to adjacent structures. This paper systematically discusses the diagnostic and therapeutic approach for this patient, aiming to share our experience and review relevant literature, with the hope of providing reference for clinical treatment strategies.